Supply Chain Management for Small and Medium Enterprises at Central Java-Indonesia - Andreas Heryjanto; Hendy Tannady; John J.O.I Ihalauw; Christantius Dwiatmadja; Harijono Harijono (International Journal of Supply Chain Management, 2020)
Abstract— The aim of this research is to explore how supply chain management (SCM) of small and medium (SMEs) business gaining successful succession. This study tries to fill the gap in previous studies concerning supply chain effectiveness in SMEs, especially in family business. To gather information, we carried out a series informal individual deep interviews, with key informants of Lunpia Semarang located in Semarang city. Using metafor from mitosis of cell, produced business-mitosis perspective successful succession in third generation of small family business. In this context, the application of the concept of SCM in the operation strategy of SMEs seems to be a very important function. This supply chain also covers all three aspects of sustainable development: business, environmental, and social. The result of study revealed that Lunpia Semarang have three business entities namely Lunpia Pemuda, Lunpia Mataram, and Lunpia Gang Lombok, and each of them is an independent business. Thus it can be concluded that the for gaining a competitive advantage, SCM is an effective tool to SMEs, which to deliver the right product and service at the most opportune time and at the lowest possible cost to the right customer.